The System Role of Smart Bioenergy: A Multicriteria Assessment. Issue 3 (11th October 2022) - Szarka, Nora; Schmid, Christopher; Pfeiffer, Diana; Thrän, Daniela
Abstract: The smart bioenergy approach encompasses the further development of modern biomass utilization systems into integrated systems consisting of optimized interaction with various renewable energy sources and coupled material/energy utilization. This study introduces the development and application of a multilevel analytic hierarchy and network process (AHP‐ANP) tool – SMARTbioGO – to assess smart bioenergy concepts in a transparent manner. The results indicate that all 36 analyzed bioenergy concepts support the energy system via sustainable biomass use, smart conversion, and system‐beneficial integration. A comprehensive contribution to a sustainable energy system can be achieved through a network of bioenergy concepts. Abstract : SMARTbioGO was developed as a multilevel analytic hierarchy and network process tool which assesses integrated contributions of smart bioenergy concepts when using sustainable biomass in smart conversion and through system‐beneficial integration. The application results of SMARTbioGO to 36 bioenergy concepts indicate that bioenergy plays multiple and system‐relevant roles in each analyzed cluster.